Equilibrium Solubility of Triclocarban in (Cyclohexane + 1,4-Dioxane) Mixtures: Determination, Correlation, Thermodynamics and Preferential Solvation (2022)
Equilibrium solubility of triclocarban (TCC) expressed in mole fraction in 1,4-dioxane and cyclohexane, as well, as in 19 {cyclohexane (1) + 1,4-dioxane (2)} mixtures, was determined at seven temperatures from T = (288.15 to 318.15) K. Logarithmic TCC solubility in these cosolvent mixtures was adequately correlated with a lineal bivariate equation as function of both the mixtures composition and temperature. Apparent thermodynamic quantities for the dissolution and mixing processes were computed by means of the van’t Hoff and Gibbs equations observing endothermal and entropy-driven dissolution processes in all cases. The enthalpy–entropy compensation plot of apparent enthalpy vs. apparent Gibbs energy was linear exhibiting positive slope implying enthalpy-driving for TCC transfer from cyclohexane to 1,4-dioxane. Ultimately, by using the inverse Kirkwood–Buff integrals it is observed that TCC is preferentially solvated by cyclohexane molecules in 1,4-dioxane-rich mixtures but preferentially solvated by 1,4-dioxane molecules in cyclohexane-rich mixtures.